2014
DOI: 10.1128/jvi.00585-14
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of Prion Strains Can Be Transmitted to Recombinant Prion Protein Fibrils in Real-Time Quaking-Induced Conversion

Abstract: The phenomenon of prion strains with distinct biological characteristics has been hypothesized to be involved in the structural diversity of abnormal prion protein (PrP Sc ). However, the molecular basis of the transmission of strain properties remains poorly understood. Real-time quaking-induced conversion (RT-QUIC) is a cell-free system that uses Escherichia coli-derived recombinant PrP (rPrP) for the sensitive detection of PrP Sc . To investigate whether the properties of various prion strains can be transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Although the end products of the reaction do not share all of the morphological and infectious properties of the input PrP Sc (25), the assay has been used to evaluate the efficacy of antiprion compounds (26). Using a modified version of RT-QuIC, we tested TUDCA's antiaggregation effect in the presence of infectious prions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the end products of the reaction do not share all of the morphological and infectious properties of the input PrP Sc (25), the assay has been used to evaluate the efficacy of antiprion compounds (26). Using a modified version of RT-QuIC, we tested TUDCA's antiaggregation effect in the presence of infectious prions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of the amyloid products produced by PMCA sonication have described a diverse population of conformers, including small oligomers, which may be more infectious than large aggregates (32,52). Examinations of RT-QuIC products have demonstrated amyloid fibrils; however, full characterization of the sizes and types of fibrils remains to be done (35,53,54). A second difference between the present studies and those of Deleault et al is the sequence of the recombinant protein used as the assay substrate (10,12).…”
Section: Figmentioning
confidence: 55%
“…Currently, it is unclear whether RT-QuIC can generate infectious prions; further study is needed to investigate how the structure of the recombinant protein substrate may alter the prion-seeded amyloid fibrils produced in RT-QuIC (35).…”
Section: Discussionmentioning
confidence: 99%
“…27 We generated the amyloid fibrils seeded with 100 pg of PrP Sc derived from either the Chandler or 22L strain in the first round of RT-QUIC (1 st -rPrP-fib Sc ). 28 Spontaneous formation of rPrP-fibrils (rPrP-fib spon ) was observed by decreasing the concentration of rPrP, because there was an inverse correlation between the rate of fibril formation and the concentration of rPrP. Previous studies using FTIR and hydrogen/deuterium exchange have shown that there are structural differences between PrP Sc -seeded and spontaneous rPrP-fibrils generated by PMCA.…”
Section: Transmission Of Conformational Properties Of Prion Strains Tmentioning
confidence: 99%